2015
DOI: 10.1536/ihj.14-311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination Therapy of Ezetimibe and Rosuvastatin on Regression of Coronary Atherosclerosis in Patients With Coronary Artery Disease

Abstract: SummaryEzetimibe has been reported to provide significant incremental reduction in low-density-lipoprotein cholesterol (LDL-C) when added to a statin; however, its effect on coronary atherosclerosis has not yet been evaluated in detail. The aim of this study was to investigate the add-on effect of ezetimibe to a statin on coronary atherosclerosis evaluated by intravascular ultrasound (IVUS).In this prospective randomized open-label study, a total of 51 patients with stable coronary artery disease (CAD) requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 35 publications
1
40
0
3
Order By: Relevance
“…Regarding the natural course of heterozygous FH patients, around 50% of men experienced adverse cardiac events by the age of 50 years and 30% of females by the age of 60 years. 4) Nevertheless, it is necessary to perform more appropriate diagnosis and intensive cholesterol-lowering therapy to prevent the development of premature CAD, 8) the majority of patients with FH are either underdiagnosed or undertreated.…”
mentioning
confidence: 99%
“…Regarding the natural course of heterozygous FH patients, around 50% of men experienced adverse cardiac events by the age of 50 years and 30% of females by the age of 60 years. 4) Nevertheless, it is necessary to perform more appropriate diagnosis and intensive cholesterol-lowering therapy to prevent the development of premature CAD, 8) the majority of patients with FH are either underdiagnosed or undertreated.…”
mentioning
confidence: 99%
“…There were no significant differences in percentage changes of LDL-C levels from baseline to follow-up between the atorvastatin and rosuvastatin groups. Highdensity lipoprotein-cholesterol seemed to be higher at follow-up than at baseline (46.8 ± 12.4 mg/dL to 51.3 ± 14.4 mg/dL and 45.7 ± 9.3 mg/dL to 49.5 ± 7.9 mg/dL for atorvastatin and rosuvastatin groups, respectively), but Ishikawa, ET AL 3 ) 33.8 ± 20.0 29.6 ± 13.6 0.47 Lipid pool (mm 3 ) 36.0 ± 19.5 34.9 ± 20.4 0.87 these differences were not significant (Table II).…”
Section: Methodsmentioning
confidence: 91%
“…17) The area of each tissue characterization (mm 2 ) was obtained from the multiplication of plaque CSA and the % tissue characterization volume; we assumed its volume (mm 3 ) per 1 mm in length and found the volume (mm 3 ) of the sum that traced and calculated each organizational area. Changes in these volumes were compared between atorvastatin and rosuvastatin groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ezetimibe reduces the absorption of cholesterol from the intestine and cause extra LDL-C reduction when added to statin (30). Previous studies have shown that ezetimibe either used alone or with statin decreases secretory phospholipase A2 activity and possibly regress carotid or coronary plaque burdens (31)(32)(33). Clinical comparisons between ezetimibe-simvastatin and simvastatin in patients with ACS have been conducted in the IMPROVE-IT study.…”
Section: Discussionmentioning
confidence: 99%